Characterization of population and production system of Tenyivo pig of Nagaland (India) - M Catherine Rutsa,; V Rutsa, (Journal of Livestock Biodiversity, 2025)
Tenyivo pig has been recently registered as fourth indigenous pig breed of India. The breed is popular among resource poor families of Nagaland and Manipur and requires low input system for rearing. Tenyivo pig possesses unique economic traits such as mothering ability, early sexual maturity specifically in males, adaptability to humid environment and meat quality. In this paper, Tenyivo pig population and its production system was characterized. This breed needs to be conserved and researched in terms of its reproductive and carcass quality. The pig can be developed as a sustainable breed of pig among tribal in India.